A framework for engaging stakeholders on the management of alien species. (1st January 2018) - Novoa, Ana; Shackleton, Ross; Canavan, Susan; Cybèle, Cathleen; Davies, Sarah J.; Dehnen-Schmutz, Katharina; Fried, Jana; Gaertner, Mirijam; Geerts, Sjirk; Griffiths, Charles L.; Kaplan, Haylee; Kumschick, Sabrina; et al.
Abstract: Alien species can have major ecological and socioeconomic impacts in their novel ranges and so effective management actions are needed. However, management can be contentious and create conflicts, especially when stakeholders who benefit from alien species are different from those who incur costs. Such conflicts of interests mean that management strategies can often not be implemented. There is, therefore, increasing interest in engaging stakeholders affected by alien species or by their management. Through a facilitated workshop and consultation process including academics and managers working on a variety of organisms and in different areas (urban and rural) and ecosystems (terrestrial and aquatic), we developed a framework for engaging stakeholders in the management of alien species. The proposed framework for stakeholder engagement consists of 12 steps: (1) identify stakeholders; (2) select key stakeholders for engagement; (3) explore key stakeholders' perceptions and develop initial aims for management; (4) engage key stakeholders in the development of a draft management strategy; (5) re-explore key stakeholders' perceptions and revise the aims of the strategy; (6) co-design general aims, management objectives and time frames with key stakeholders; (7) co-design a management strategy; (8) facilitate stakeholders' ownership of the strategy and adapt as required; and (9) implement the strategy and monitor management actions to evaluate the need for additional or future actions. In case additional management is needed after these actions take place, some extra steps should be taken: (10) identify any new stakeholders, benefits, and costs; (11) monitor engagement; and (12) revise management strategy. Overall, we believe that our framework provides an effective approach to minimize the impact of conflicts created by alien species management. Highlights: Conflicts of interest can prevent the success of invasive species management actions. Stakeholder engagement may avoid conflicts on interests. A 12-step framework for stakeholder engagement is discussed.